2010
DOI: 10.1021/jp1039282
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Specific Interactions on the Rotational Dynamics of Charged and Neutral Solutes in Ionic Liquids Containing Tris(pentafluoroethyl)trifluorophosphate (FAP) Anion

Abstract: Rotational dynamics of two organic solutes, rhodamine 110 (R110) and 2,5-dimethyl-1,4-dioxo-3,6-diphenylpyrrolo[3,4-c]pyrrole (DMDPP), has been investigated as a function of temperature in a series of 1-alkyl-3-methylimidazolium ionic liquids (alkyl = ethyl, butyl, hexyl, and 2-hydroxyethyl) containing tris(pentafluoroethyl)trifluorophosphate (FAP) anion. The present study has been essentially undertaken to examine the influence of specific interactions on the rotation of cationic (R110) and neutral (DMDPP) so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
161
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(171 citation statements)
references
References 52 publications
9
161
1
Order By: Relevance
“…The experimental findings appear to be quite interesting when we compare our data with the existing literature 6h,i. Figure 8 depicts the log–log plots of average rotational time τ r of C153 versus η /T in ILs.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The experimental findings appear to be quite interesting when we compare our data with the existing literature 6h,i. Figure 8 depicts the log–log plots of average rotational time τ r of C153 versus η /T in ILs.…”
Section: Resultsmentioning
confidence: 78%
“…Subsequently, Tsuzuki et al6g showed that the conformational flexibility of the alkyl chains in cations is one of the important factors determining the diffusion of ions. Recent studies on dynamics of orientation by Frauchey and Fayer6h and Dutt6i showed that length of the alkyl side chain in the cationic moiety of ILs has noticeable influence on the rotational behavior of organic solutes in ILs.…”
Section: Introductionmentioning
confidence: 99%
“…The instrumental details have been described in our earlier publication. 33 Samples containing the probe 9-PA were excited with a 374 nm diode laser, and the emission from the samples was collected at 420 nm. On the other hand, samples with the probe R110 were excited with a 445 nm diode laser, and the emission was monitored at 550 nm.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…48 It has been shown in our earlier publications that the slower rotational diffusion of R110 is due to the specific interactions it experiences with the medium. 33,35,36,62 Because R110 is a hydrogen bond donating solute, it forms hydrogen bonds with the anions of the ionic liquid, and the strength of these hydrogen bonds depends on the hydrogen bond accepting ability or the basicity of the anion. 35,36 In contrast, 9-PA, being a nonpolar solute, experiences only viscous friction, and as a consequence its rotation is significantly faster compared to that of R110.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…7,8 However, such an influence is not apparent when similar studies were performed in 1-alkyl-3-methylimidazolium-based ionic liquids with weakly associating anions such as bis(trifluoromethylsulfonyl)imide and tris(pentafluoroethyl)trifluorophosphate. 33,34 In other words, whether solute rotation is affected or not depends on the nature of the anion and the length of the alkyl chain on the imidazolium cation. In light of these findings, it would be pertinent to examine the rotational diffusion of organic solutes in ionic liquids with short alkyl chains and weakly associating anions that are diluted by a nondipolar solvent and compare the results to the ones obtained in the corresponding neat ionic liquids.…”
Section: Introductionmentioning
confidence: 99%